Proximity to four bikeway types and neighbourhood-level cycling mode share of male and female commuters - Kay Teschke; Anna Chinn; Michael Brauer (Journal of Transport and Land Use)
We studied 2011 cycling mode share at the census-tract level in Montréal and Vancouver, Canadian cities with relatively high mode shares and diverse bike infrastructure. We examined whether mode share variability, for all commuters and male and female commuters separately, was related to proximity to any bikeway, proximity to four bikeway types, slopes on routes to bikeways, or commute times. Cycling mode shares at the census-tract level varied from 0 to 20.4%. About a third of cycle commuters were female, but this proportion approached parity with males in census tracts with mode shares of 7% and higher. A one-kilometer closer proximity to any bikeway was associated with four times higher cycling mode share. Proximity to cycle tracks was associated with higher cycling mode shares in both cities. Other bikeway types did not have similar associations in the two cities, and the pattern of results suggested that the networks formed may have been more important than specific bikeway characteristics. Uphill slopes to bikeways were associated with somewhat lower mode shares in bivariate analyses but not in adjusted models. Cycle commuting was most common in neighborhoods with intermediate average commute durations: 20 to 29 minutes. Our results suggest that cycle tracks and bikeways that form a connected network are associated with higher neighborhood cycling commute mode shares. These features appeared even more important to women, and their cycling (or not) was strongly related to overall cycling mode shares.